2017
DOI: 10.4049/jimmunol.1601732
|View full text |Cite
|
Sign up to set email alerts
|

Roquin Paralogs Differentially Regulate Functional NKT Cell Subsets

Abstract: NKT cells represent a small subset of glycolipid-recognizing T cells that are heavily implicated in human allergic, autoimmune, and malignant diseases. In the thymus, precursor cells recognize self-glycolipids by virtue of their semi-invariant TCR, which triggers NKT cell lineage commitment and maturation. During their development, NKT cells are polarized into the NKT1, NKT2, and NKT17 subsets, defined through their cytokine-secretion patterns and the expression of key transcription factors. However, we have l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Consistent with this concept of dynamic regulation, analysis of Roquin-deficient NKT cells showed developmental skewing toward the NKT17 subset in the thymus associated with an absence of NKT cells in the periphery. Although this phenotype would be explained by derepressed mTORC1 activity as demonstrated by the strikingly similar phenotype of Tsc1 fl/fl ;CD4-Cre mice (Wu et al, 2014), mature Roquin-deficient NKT17 cells in the thymus did not reveal increased mTOR phosphorylation (Drees et al, 2017). A Roquin-mediated stimulation of the mTOR pathway has been reported before, the proposed molecular mechanism involving a Roquin RING-finger-dependent inhibition of the AMPK kinase that itself inhibits mTOR (Ramiscal et al, 2015).…”
Section: Discussionsupporting
confidence: 51%
“…Consistent with this concept of dynamic regulation, analysis of Roquin-deficient NKT cells showed developmental skewing toward the NKT17 subset in the thymus associated with an absence of NKT cells in the periphery. Although this phenotype would be explained by derepressed mTORC1 activity as demonstrated by the strikingly similar phenotype of Tsc1 fl/fl ;CD4-Cre mice (Wu et al, 2014), mature Roquin-deficient NKT17 cells in the thymus did not reveal increased mTOR phosphorylation (Drees et al, 2017). A Roquin-mediated stimulation of the mTOR pathway has been reported before, the proposed molecular mechanism involving a Roquin RING-finger-dependent inhibition of the AMPK kinase that itself inhibits mTOR (Ramiscal et al, 2015).…”
Section: Discussionsupporting
confidence: 51%
“…For instance, in support of thymic commitment it has been shown that the TCR signal strength during thymic development can direct the differentiation of iNKT cells within specific functional subsets . Further to this, a variety of signalling molecules and transcription factors including Zap70, Bcl11b or Roquin has been shown to participate in the control of iNKT cell lineage differentiation . On the other hand, several lines of evidence suggest that iNKT cells can acquire functional capabilities in the periphery.…”
Section: Nkt Cells: An Overviewmentioning
confidence: 99%
“…Beyond being recognized as a marker for plasma cells and developing B cells, little is known about the role of sdc1 in immune cell functions (9,10). Recently, our group and subsequently others have identified sdc1 as a specific marker of IL-17-producing subset of NKT cells (NKT17) (11)(12)(13)(14)(15). We have also shown that sdc1 deficiency significantly increases frequency of NKT17 cells both in the thymus and periphery (11) and hence act as a negative regulator of NKT17 cell homeostasis (16).…”
mentioning
confidence: 99%